Zero mode effect generalization for the electromagnetic current in the light front - Suzuki, Alfredo Takashi [UNESP]; Sales, Jorge Henrique; Soriano, Luis Alberto [UNESP] (American Physical Society (APS), 2013)
We consider in this work the electromagnetic current for a system composed of two charged bosons and show that it has a structure of many bodies even in the impulse approximation, when described in the light-front time x+. In terms of the two-body component for the bound state, the current contains two-body operators. We consider the photon interacting with two bosons and the process of pair creation connected to this interaction, interpreting it as a zero mode contribution to the current and discuss the consequences of this pair creation to the components of currents in the light front. © 2013 American Physical Society.